Social vulnerability indicators in pandemics focusing on COVID‐19: A systematic literature review. Issue 5 (7th April 2022) - Fallah‐Aliabadi, Saeed; Fatemi, Farin; Heydari, Ahad; Khajehaminian, Mohammad Reza; Lotfi, Mohammad Hasan; Mirzaei, Masoud; Sarsangi, Alireza
Abstract: Introduction: Social factors can affect the vulnerability of disaster‐prone communities. This review aimed to identify and categorize social vulnerability indicators in the COVID‐19 pandemic. Methods: This systematic review was conducted in February 2021. Bibliographies, citation databases, and other available records were investigated based on the aim of the study. The Joanna Briggs Institute (JBI) critical appraisal tools were applied for assessing the included articles retrieved through the comprehensive and systematic literature search. Descriptive and thematic analyses were done to extract the indicators affecting social vulnerability in the COVID‐19 pandemic. Results: Thirty‐one eligible articles were included and 85 indicators of social vulnerability were extracted. The indicators were categorized in seven main categories, including; Household, community composition; Race, minority status and language; Socioeconomic status; Community health status; Public health infra‐structures; Education; Information, technology and communication. Conclusion: Regions with higher social vulnerability experienced greater mortality rates during the COVID‐19 pandemic. Additional research is needed to measure the social vulnerability index in pandemics to prioritize distribution of scarce resources and ensure effectiveness and equity for all regions of countries.